Positioning Malaysia in Medical Tourism: Implication on Economic Growth in ASEAN Integration - Au Yong Hui Nee (Indonesian Journal Of Business And Economics, 2018)
With a rapid growth of medical tourism in the country, the Malaysian Government is under pressure to make the sector of benefit to the public healthcare services. Purpose: This paper attempts to deepen the understanding of the development of medical tourism on destination countries’ healthcare systems and the effect toward economy growth. Methodology: Mix methods were applied in the paper with data for the duration of 2000 – 2015 obtained from sources including Malaysia Health Tourism Council (MHTC) and World Bank Indicators. Analysis of the paper includes t-test of gross national products and medical tourism receipts. The paper also shares strategies needed for effective promotion of medical tourism in a medical tourism decision model. Findings: The result shows that ASEAN Economic Community is likely to bring in higher trade volumes in health services. This paper concludes that medical tourism plays an important role in economy by tripling medical tourism receipts to RM900 million in tandem with the economic growth. Limitations: The findings should be interpreted with caution. Practical implications: Upcoming opportunities are potential medical travellers from less advanced ASEAN countries. Social implications: Growth of medical tourism should not lead to ‘brain drain’. Originality: The study is one of its kinds as it highlights by the use of mix mode in analysing the sector’s economic contribution in a trans-boundary tourism context in a modified medical tourism model. Limitations: For the qualitative analysis of this paper on top of limited length of data for quantitative analysis, the findings should be interpreted with caution.Keywords: Decision Process, Economic Integration, Healthcare, Education Welfare, Health Tourism, Marketing Strategy, Medical Tourism